Translational Research: The Cornerstone for Medical Technology Advancement. (April 2019) - Tellez, Armando; Ferrone, Marco; Granada, Juan F.
Significant improvements in quality of life and mortality have occurred over the last century due to the giant advancements in medical innovation. Medical innovation continues to move forward, and it is expanding to areas never explored before. In particular, the advancement in big data analytics is now enabling the rapid progress in the understanding of gene influence in human diseases. The progress in medical innovation achieved until today is significant; however, the potential that future technologies have to modify patterns of disease thought to be incurable is mind-boggling. In the present issue of Toxicologic Pathology, a wide variety of devices and validation platforms are presented as a clear evidence of the multidisciplinary approach that is necessary for the progress of this field. As a clinician, scientist, and medical device innovator, I am confident that this special issue dedicated to the "Pathology of Medical Devices" will be of great value to the scientific and medical device innovation community.